DETERMINING FACTORS FOR MARKETING SUCCESS IN ENDEK AND EMBROIDERED TEXTILE INDUSTRY THROUGH THE INTEGRATION OF ENTREPRENEURSHIP ORIENTATION AND CUSTOMER RELATIONSHIP MARKETING IN MARKETING CAPABILITIES - Rihayana, I Gede; Salain, Putu Pradiva Putra; Adhika, Nyoman Resa (Review of Management and Entrepreneurship, 2019)
The research on the integration of entrepreneurial orientation and customer relationship marketing in building and strengthening marketing capabilities to achieve marketing success in the endek and embroidered woven fabric handicraft industry in Denpasar City was carried out in all businesses that produce and sell woven and embroidery fabrics, and are listed in the Directory of Service Denpasar City Industry and Trade in 2016. Woven and embroidery businesses are spread in four districts with a total of 55 business units. The sample of this study is all members of the population, and placed the owners / managers of woven and embroidery fabrics as the target of the respondents. This research is a research survey using a questionnaire as the main research instrument. In addition, this study also uses independent interviews with key informants to support or explore findings from the results of the quantitative analysis. The research data were analyzed using Structural Equation Modeling (Smart-PLS), where the results showed that entrepreneurial orientation had an effect on marketing performance, but entrepreneurial orientation had no influence on marketing capabilities. Also, customer relationship marketing had an influence on marketing performance and marketing capabilities, while marketing capabilities have an influence on marketing performance.